One-dimensional zinc oxide nanostructures and devices - Yang, Yi (2010)
As a multifunctional oxide semiconductor, ZnO has attracted substantial interest for a wide range of applications, including transparent conductors, UV light-emitting diodes (LEDs) and laser diodes, chemical and biochemical sensing, field emitting devices, dye-sentitized solar cells and host for diluted magnetic semiconductor. On the other hand, nanostructures made of various materials including ZnO, such as nanowires (NWs), nanobelts, nanoribbons, etc, are an emerging class of one-dimensional and quasi-one-dimensional materials that have been extensively studied as fundamental building blocks for nano-scale science and technology in the last period. This thesis focuses on the fabrication of various high quality crystalline ZnO nanostructures by using the vaporphase transport (VPT) method and their subsequent characterizations. The emphasis is devoted to the enhancement of photoluminescence properties by plasma immersion ion implantation (PIII) surface modification, the application of ZnO NWs as templates for growth of other oxide materials, and applications in p-n homojunction LEDs. Two new morphologies, microraft with diamond-shaped cross section and resistor-shaped NW composed of a pair of crystallites, have been successfully fabricated by VPT method from ZnO and graphite powder at atmosphere pressure. Although the growth conditions are similar for both morphologies, by varying the partial pressure of the growth species and the amount of Cu and water during growth, the end products are totally different.